Synthesis, physical and chemical properties of 2-((4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetic acids salts - А.А. Safonov; О. І. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Thanks to the rapid development of science, humanity has achieved remarkable success in various fields. This also applies to the synthesis of biological compounds. Over the centuries, scientists have invented many methods and drugs that are being actively used to date. Derivatives of 1,2,4-triazole can be the foundation for the manufacture of new native drugs that will compete with foreign ones.